Comparative Analysis of FDI between India and UK: A Comparative Analysis of Foreign Direct Investment between India and the UK in the Post-Brexit Era (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Investment by a country into the infrastructure of another country is known as foreign direct investment. FDI has proved to be a life-line for developing countries like India, Sri Lanka, Brazil, China and some other countries. The economic relationship between India and the UK has been in existence for more than three hundred years old. The UK became the first country to invest in India. There is no doubt that investment was exploitative in nature. During pre-independence era, no other country interested to invest in India. After independence, the UK remained largest investor in India by 1964. After Brexit relationship between India and the UK will be strong. There are positives and negatives both for India. Negative is that the impact of Brexit will affect the Indian diaspora there as well. Brexit might also have a positive effect, but these results may not show up immediately. Thus, Britain’s getting out of European Union has made it face reduced trade and a sustained drop in its GDP, the net effect for India may turn out to be positive. In present paper, we shall analyze the trends of FDI between India and UK and do comparative study between two countries.